Efficacy and Safety of Tofacitinib vs Methotrexate in Patients with Moderate to Severe Plaque Psoriasis - Khondker, Lubna (Journal of Enam Medical College, 2021)
Background: Janus kinase (JAK) pathways are key mediators in the immune-pathogenesis of psoriasis. JAK inhibitors have been studied in early phase trials for psoriasis patients, and the data are promising for these agents as potential treatment options. Objective: Efficacy and safety of tofacitinib in patients with moderate to severe plaque psoriasis. Materials and Methods: A prospective, clinical trial was conducted at the department of Dermatology and Venereology, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka for duration of January 2019 to December 2019 with plaque-type psoriasis patients and the group A patient received tofacitinib 5 mg 12 hourly daily for 8 weeks and the group B patient received oral methotrexate 15 mg/week in a three 12-hourly divided doses for same duration. Results: The psoriasis Area and Severity Index (PASI) score was decreased significantly from base line to 4th week follow up and also to the 8 week follow up in both groups of patients (p<0.05). The mean percentage of decrease of PASI score was found to be high among the group B patients (84.9±10.4, i.e. 85%) than the group A patients (77.6±14.0, i.e 78%), but the mean difference was not statistically significant (p>0.05). Analysis revealed that a statistically significant improvement of psoriasis was observed based on PASI score eight weeks of treatment in both treatment group (p=0.001) and in both groups of patients the adverse effects were few and mild in nature. Conclusion: Tofacitinib is an effective and safe drug in the treatment of psoriasis and almost similar to methotrexate and so tofacitinib can be alternative drug to methotrexate in the treatment of moderate to severe psoriasis. J Enam Med Col 2021; 11(2): 108-119